Surface hardness of friction stir welded AA6063 pipe - Ismail, A. (EDP Sciences, 2014)
The external surface hardness of friction stir welded aluminum alloy 6063 pipe joint was investigated in this paper. The 89mm of outside diameter pipe with 5mm of wall thickness was used as test pipe piece for this experiment on closed butt joint configuration by utilising Bridgeport 2216 CNC milling machine and orbital clamping unit specially designed to cater for this task and function. Several welded samples were produced on varying process parameters which were successfully joined by using a non-consumable tool with a flat shoulder and a cylindrical pin. Â© 2014 Owned by the authors, published by EDP Sciences.